Techno-Economic Optimization Study of Renewable Energy Planning in Buru Island Electricity System - Z Day, Faizatul Hasanah; Samual, Muhammad Gillfran; Garniwa, Iwa; Sudiarto, Budi (Universitas Indonesia, 2024)
One of the strategies to achieve Indonesia's NDC target in 2030 is through the development of renewable energy power plants, and the transition from fossil fuels to renewable energy. The use of diesel power plants, especially with the case on Buru Island as the only electricity supply, contributes to the production of emissions, and increases the Cost of Energy (CoE) of the utility system. On the other hand, Buru Island is rich in renewable energy potential, such as geothermal, hydropower, bioenergy, and solar energy. This study aims to design an optimal power generation system on Buru Island by considering the renewable energy mix, financial feasibility, reduction in the CoE of local electricity system, reduction in CO2 emissions, and the potential load growth of the local industry, i.e. fisheries industry sector. This study utilizes HOMER software to obtain a power generation scenario that can supply the load with the most optimal renewable energy penetration, the lowest Levelized CoE (LCOE), and the lowest CO2 emissions. Seven electrical systems on Buru Island were implemented to form 4 systems, namely an integrated system of 4 previously distributed systems, and 3 other distributed systems. The result of this research gives out the most optimum configuration of hybrid or complete renewable energy-based power plant configuration for each system. The configurations can reduce the CoE up to 20.17 cUSD/kWh, and up to zero CO2 emission.